Feasibility Study of Bu Nia's Traditional Herbal Drink Business in Depok City - Aqmarina, Damartera Tyan; Turgarini, Dewi; Fajri, Ilham (Universitas Pendidikan Indonesia, 2019)
Bu Niaâ€™s traditional herbal drink is a micro home business industry which has a potential to be developed. To overcome many challenges and risks in the future, it needs to be based on a business feasibility study. The purpose of this research is to find out the description of. The purpose of this research is to find out an overview of the business activities of Bu Niaâ€™s traditional herbal drink in terms of legal aspects, market and marketing aspects, technical and technological aspects, social economic aspects, management and organizational aspects, environmental impact analysis and financial aspects . The method used is descriptive analysis, data collection techniques are done by interviewing the business owner, observingÂ the business place, and documenting. Technical data analysis uses qualitative and quantitative mixed approach.